Surveillance evangelism: Private technology companies and the digital futures of crimmigration control - Singler, Samuel (Theoretical criminology, 2025)
This article contributes to criminological research on surveillance and border technologies. By analysing private security companies’ visions of future technologies as surveillance imaginaries, I argue that these companies can be conceptualized as ‘surveillance evangelists’. Rather than marketing existing technologies, surveillance evangelists aim to convince state agencies and the wider public about the desirability and plausibility of particular – contingent and contestable – technological futures. Private security companies’ visions of digital borders across the African continent contribute to the ideological normalization of crimmigration control, by promoting digital futures in which technologies of criminal justice and border control are fully interoperable. The notion of evangelism is useful for highlighting the speculative, ideological nature of these imaginaries as well as the postcolonial hierarchies that underpin the construction of technical expertise relating to digital crimmigration control.